2021
DOI: 10.1002/adpr.202100011
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Applications of Atomic Layer Deposition in Perovskite‐Based Solar Cells

Abstract: in 2018. She is currently majoring in integrated circuit engineering as a postgraduate student, with her research focused on atomic layer deposition and thin film encapsulation for optical electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…To achieve a conformal deposition on structured silicon precursors, a solution was reported by Sahli et al using a hybrid sequential method to deposit the perovskite: the inorganics PbI2 and CsBr were first deposited by evaporation followed by the deposition by spin coating of the organohalides FAI and FABr. [ 44 ] In addition, others layers as transport materials were deposited using thermal evaporation, sputtering, or atomic layer deposition [ 177 ] allowing a conformal deposition of the textured precursor as well. Furthermore, they point out also the complexity of conformal depositions even using this protocol: they show that if the deposition of the HTM spiro‐TTB was conformal on the ITO recombination layer, after the perovskite annealing step, it detaches from the ITO.…”
Section: Light Management In Perovskite‐based Tandem Solar Cellsmentioning
confidence: 99%
“…To achieve a conformal deposition on structured silicon precursors, a solution was reported by Sahli et al using a hybrid sequential method to deposit the perovskite: the inorganics PbI2 and CsBr were first deposited by evaporation followed by the deposition by spin coating of the organohalides FAI and FABr. [ 44 ] In addition, others layers as transport materials were deposited using thermal evaporation, sputtering, or atomic layer deposition [ 177 ] allowing a conformal deposition of the textured precursor as well. Furthermore, they point out also the complexity of conformal depositions even using this protocol: they show that if the deposition of the HTM spiro‐TTB was conformal on the ITO recombination layer, after the perovskite annealing step, it detaches from the ITO.…”
Section: Light Management In Perovskite‐based Tandem Solar Cellsmentioning
confidence: 99%
“…ALD-oxide (Atomic Layer Depostion-oxide) is an essential material for the perovskite solar cell (PSC) electron transport layer, organic optoelectronic device encapsulation layer, and TEs dielectric layer. However, due to the surface structure of graphene and the step-covering deposition of ALD, ALD oxides are difficult to deposit on graphene, so it is a challenging task to utilize graphene and ALD-oxide simultaneously [ 34 , 65 , 66 , 67 ]. Accordingly, as shown in Figure 4 , people usually deposited a functional layer before depositing the ALD-oxide on the graphene, which can be a useful aid to the deposition of the ALD-oxide [ 68 ].…”
Section: Graphene Based Te Materialsmentioning
confidence: 99%
“…Moreover, nondestructive nature of ALD processing and relatively low deposition temperatures render no harm to the as-fabricated devices. [215] Wang et al reported a mild, efficient plasma-assisted deposition method by using molecular layer deposition (MLD) and plasma-enhanced atomic layer deposition (PEALD). [216] After Figure 11.…”
Section: Encapsulationmentioning
confidence: 99%
“…Moreover, nondestructive nature of ALD processing and relatively low deposition temperatures render no harm to the as‐fabricated devices. [ 215 ] Wang et al reported a mild, efficient plasma‐assisted deposition method by using molecular layer deposition (MLD) and plasma‐enhanced atomic layer deposition (PEALD). [ 216 ] After deposition an alucone layer on PSC via MLD at 50 °C, the remained methyl groups can effectively protect the PSC against O 2 plasma during the following Al 2 O 3 PEALD process since O 2 plasma was consumed via chemical reaction.…”
Section: Extrinsic Stabilization Strategiesmentioning
confidence: 99%